Work hard or play hard: the effect of leisure crafting on opportunity recognition and venture performance - Hamrick, Alexander B.; Paterson, Ted A.; Michaelis, Timothy L.; Murnieks, Charles Y.; Petrou, Paraskevas (Journal of Business Venturing, 2023)
Given the challenges inherent in starting companies, investigation of how entrepreneurs use their time at work to develop ventures has received prominent attention by scholars. We argue that how entrepreneurs use their leisure time has not received commensurate scrutiny. Leisure crafting, the proactive pursuit of particular leisure activities for specific goals, could play an important role in the entrepreneurial process. Herein, we develop and test a theoretical model describing how leisure crafting among entrepreneurs affects opportunity recognition and venture performance. Using three studies we provide strong evidence that leisure crafting positively relates to opportunity recognition and venture performance, which is mediated by thriving at work and moderated by work task focus. These findings provide generative insights into the nature of leisure and the micro-processes that drive entrepreneurship.